Alpha-linolenic acid intake and 10-year incidence of coronary heart disease and stroke in 20,000 middle-aged men and women in the Netherlands. - Janette de Goede; W M Monique Verschuren; Jolanda M A Boer; Daan Kromhout; Johanna M Geleijnse (PLoS ONE, 2011)
BACKGROUND: Whether intake of alpha-linolenic acid (ALA), the plant-derived n-3 polyunsaturated fatty acid (PUFA), could prevent cardiovascular diseases is not yet clear. We examined the associations of ALA intake with 10-year incidence of coronary heart disease (CHD) and stroke in the Netherlands. METHODS: Data were collected from a general population of 20,069 generally healthy men and women, aged 20 to 65 years. Habitual diet was assessed at baseline (1993-1997) with a validated 178-item food frequency questionnaire. Incidences of CHD and stroke were assessed through linkage with mortality and morbidity registers. Hazard ratios (HR) were calculated with multivariable Cox proportional hazards models, adjusted for age, gender, lifestyle, and dietary factors. RESULTS: During 8-13 years of follow-up, we observed 280 incident CHD events (19% fatal) and 221 strokes (4% fatal). Intakes of energy-adjusted ALA in quintiles ranged from less than 1.0 g/d in the bottom quintile (Q1) to more than 1.9 g/d in the top quintile (Q5). ALA intake was not associated with incident CHD, with HRs varying between 0.89 and 1.01 (all p>0.05) in Q2-Q5 compared with the bottom quintile of ALA intake. For incident stroke, however, participants in Q2-Q5 had a 35-50% lower risk compared with the reference group. HRs were 0.65 (0.43-0.97), 0.49 (0.31-0.76), 0.53 (0.34-0.83), and 0.65 (0.41-1.04) for Q2-Q5 respectively. CONCLUSION: In this general Dutch population, ALA intake was not associated with incident CHD. The data suggested that a low intake of ALA may be a risk factor for incident stroke. These results warrant confirmation in other population-based studies and in trials.